Cryptorchidism and cancer - Schenone, Héctor; García Guido, Luis (Cirugía del Uruguay, 1973)
The problem of the eventual relationship between cryptorchidism and cancer has been the subject of study (1, 2, 3), for several decades and in our setting, Surraco (4), Lo · ckhart (5) and HugheG (6), dealt with the same issue.